Neutrophils and neutrophil extracellular traps in oral health and disease - Tae Sung Kim; Niki M. Moutsopoulos (Experimental and Molecular Medicine)
Abstract Neutrophils perform essential functions in antimicrobial defense and tissue maintenance at mucosal barriers. However, a dysregulated neutrophil response and, in particular, the excessive release of neutrophil extracellular traps (NETs) are implicated in the pathology of various diseases. In this review, we provide an overview of the basic concepts related to neutrophil functions, including NET formation, and discuss the mechanisms associated with NET activation and function in the context of the prevalent oral disease periodontitis.